Effect of Physical Training Towards Body Balance in Overweight Condition - Purwo Sri Rejeki; Anita Faradilla Rahim; Rizki Eka Prasetya (Biomolecular and Health Science Journal, 2018)
An overweight individual has morphological changes in the muscle resulting functional impairment and can cause reduction in body balance system. Balance is an ability to maintain both static and dynamic equilibrium on various positions. An overweight person will experience a decrease in abdominal muscle strength and center of gravity shift. Physical training has positive effects to increase body balance. Stretching exercise maintains and increases the elasticity of muscle, tendon, fascia, ligament and joint motion and improve balance. Resistance exercise increases muscle performance which has benefit effect on balance system dynamically. The proprioceptive, an important part of balance maintenance to feel joint position or body when moving, can be improved by training that performed using balance board. Mechanoreceptor that is stimulated and the adaptation of the body's balance control that is influenced by balance board training results a good proprioceptive.